2012
DOI: 10.1111/jre.12016
|View full text |Cite
|
Sign up to set email alerts
|

The role of physiological markers of health in the association between demographic factors and periodontal disease

Abstract: Objectives This study examines whether the association between periodontal disease and demographic factors is mediated by physiological measures of health. Background Age is highly related to oral health status. The higher prevalence of oral disease within sub-groups of the population may reflect a tendency towards “early aging” and dysregulation of multiple physiological systems. Methods Logistic regression was used to examine whether biomarkers and demographic factors, such as SES and race/ethnicity, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…In contrast, a study by Levine et al. () reported that the risk of periodontal disease is higher among black and/or low‐income individuals (Levine et al. ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, a study by Levine et al. () reported that the risk of periodontal disease is higher among black and/or low‐income individuals (Levine et al. ).…”
Section: Discussionmentioning
confidence: 90%
“…() reported that the risk of periodontal disease is higher among black and/or low‐income individuals (Levine et al. ). A study from France reported that tooth decay was statistically associated with lower age (OR = 1.58, 95% CI [1.03, 2.45]) and lower educational level (OR = 1.53, 95% CI [1.06, 2.23]) (Vergnes et al.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the remaining associations indicate that these factors are insufficient to explain these inequalities, which is consistent with the findings of previous studies using health behaviors 6 8 , 10 and physiological markers. 9 These results suggest the presence of more complex determinants of oral health inequalities and imply that the elimination of oral health inequalities necessitates the development of strategies that look beyond proximal causes, such as early-life unequal exposure to risk factors. 31 …”
Section: Discussionmentioning
confidence: 95%
“…Levine et al. found that the cytomegalovirus serum antibody level in the USA was highest in low‐income individuals and higher in non‐Hispanic black subjects than in white subjects, and was predictive of periodontal disease.…”
Section: Methodological Issuesmentioning
confidence: 99%